Pathological analysis of invasive ductal carcinoma: Clinical case - Guedes, Italo Cavalcante; Lira, Jaqueline Barreto da Silva de Oliveira; Pereira, Mayra Gabrielly Costa; Lima , Marcio Medeiros; Nóbrega, Lídia Pinheiro da; Gondim, Josué Brito (Research, Society and Development, 2024)
In Brazil, excluding non-melanoma skin tumors, breast cancer is a prevalent disease among women in all regions of the country. According to data from the National Cancer Institute (INCA), approximately 73,610 new cases of breast cancer are estimated for the 2023-2025 period. In the analysis of morphological, genetic, and enzymatic methods, the aggressiveness of the breast cancer type is considered, meaning that breast cancer treatment is conducted according to the tumor's aggressiveness, involving medicated or non-medicated therapy. The research is justified by trying to contribute scientific and academic insights, emphasizing the importance of anatomopathological analysis in studying invasive ductal carcinoma and how it may affect the quality of life of patients with this pathology. This study aimed to show the importance of anatomopathological analysis in investigating invasive ductal carcinoma through a case report. Within the discussed context, research was conducted on the significance of anatomopathological analysis in studying invasive ductal carcinoma, and the association between anatomopathological results and the patient's quality of life in the case report, with the help of bibliographic data. Based on the studies, it is concluded that the patients’ quality of life is associated with the diagnosis, and treatment of this neoplasm, directly impacting their psychological, social, and marital well-being. This enables the approach suggestions and areas for future research that could provide fundamental contributions.